Effects of water immersion on soleus neuromuscular parameters - Jozefiak, Zsolt (2017)
Aquatic rehabilitation is a widely used tool for injury prevention or rehabilitation. The underlying neuromuscular mechanisms during immersion are less known due to methodological issues. The following study main purpose to assess neuromuscular functions and muscle architecture changes within immersed condition. The physical properties of water to the human body are well understood, as well as its effect on the cardiorespiratory system. While the Hoffmann reflex, as a tool to assess neuromuscular changes on dry land is widely examined, it has been rarely used during immersion. The effect of water immersion on muscle behavior is also unknown. In this study control values were recorded in sitting position for one hour on dry land. This recording period was needed to mimic the similar protocol as in water and to compare the two conditions. The dry land recording showed no changes in the recorded parameters over time. Unaltered reflex and muscle architecture parameters on dry land indicate that the changes during immersion are due to the altered environment. During the first 15 minutes of immersion maximal M-wave and muscle thickness decreased significantly. Maximal H/M ratio showed no significant changes in water immersed condition. The decreased potentiation of the muscle due to the architecture changes is reflected by the decreased maximal M-wave; however the unaltered H-reflex indicates background compensatory mechanisms. Possibly the activation of peripheral mechanoceptors and the effect of weightlessness decreased the tonic presynaptic inhibition which leads to compensated H-reflex response. Repeating the protocol showed good reliability of the maximal H/M ratio, and good inter-session reliability of the muscle thickness. The thesis indicates that with adequate precaution, H-reflex and ultrasound recording is possible during prolonged immersed condition, while the results raise the possibility of acute peripheral and central neuromuscular activation during immersion. With the current protocol the precise mechanisms cannot be addressed, it rather raises the importance for future studies to measure muscle architecture and presynaptic inhibition.